CONCEPTUAL FRAMEWORK: SUBSIDY TO THE NURSING'S ASSISTENCE - Telma Elisa Carraro (Universidade Federal do Paraná, 1998)
The historical development of Nursing's Models and Theories is approached in this paper and it tries to wake up for a discussion about framework, which offers subsidy to the professional practice. It also approaches some differences relating to terminology between framework and model, theoretical and conceptual, pointing out to the construction and the utilization of the conceptual framework to direct Nursing's Assistence.